Analisis Struktur dan Bentuk Tari Pasihan Bondhan Sayuk: Sebuah Kajian Makna Teks - Slamet Slamet (Greget, 2010)
This study on the meaning of the text in the pasihan dance Bondhan Sayuk aims to discover and understand the text of the Bondhan Sayuk dance as a whole by studying the meaning ofÂ the song used in the musical accompaniment which is the text for the dance music. The research uses a descriptive qualitative method with a multi-disciplinary approach. The techniques used for collecting data include a bibliographical study, observation, and interviews. The creation of the Bondhan Sayuk dance was inspired by the existing Enggar-enggar dance. Sunarno, the choreographer of the Bondhan Sayuk dance, was aware that this dance was originally accompanied by a gamelan composition written by Marto Pangrawit, which was motivated by his desire to have a son. By studying Bondhan Sayuk, it can be seen whether there are any different variations of movement among the dancers. This may occur if there is a different interpretation of the musical text, in particular in the tembang tengahan section. This research focuses more on how the dancers and the audience understand the song text used in the musical accompaniment in relation to the expression of the dance movements. The text used in a performance of Bondhan Sayuk, which exists within a musical context that is filled with meaning, is subsequently manifested in the form of a dance performance and provides a framework of thought for the dancers which theyÂ express in the form of dance, while the audience gains an understanding of the meaning of a performance of Bondhan Sayuk, through its song text and through the dance which create a complete performance, at the time the performance takes place. Keywords : Pasihan, Bondhan Sayuk, and Meaning of the text